Complete Revascularisation in Impella-Supported Infarct-Related Cardiogenic Shock Patients Is Associated With Improved Mortality - Schäfer, Andreas; Westenfeld, Ralf; Sieweke, Jan-Thorben; Zietzer, Andreas; Wiora, Julian; Masiero, Giulia; Sanchez Martinez, Carolina; Tarantini, Giuseppe; Werner, Nikos (Frontiers in Cardiovascular Medicine, 2021)
Background: Acute myocardial infarction-related cardiogenic shock (AMI-CS) still has high likelihood of in-hospital mortality. The only trial evidence currently available for the intra-aortic balloon pump showed no benefit of its routine use in AMI-CS. While a potential benefit of complete revascularisation has been suggested in urgent revascularisation, the CULPRIT-SHOCK trial demonstrated no benefit of multivessel compared to culprit-lesion only revascularisation in AMI-CS. However, mechanical circulatory support was only used in a minority of patients. Objectives: We hypothesised that more complete revascularisation facilitated by Impella support is related to lower mortality in AMI-CS patients. Methods: We analysed data from 202 consecutive Impella-treated AMI-CS patients at four European high-volume shock centres (age 66 ± 11 years, 83% male). Forty-seven percentage (n = 94) had cardiac arrest before Impella implantation. Revascularisation was categorised as incomplete if residual SYNTAX-score (rS) was >8. Results: Overall 30-day mortality was 47%. Mortality was higher when Impella was implanted post-PCI (Impella-post-PCI: 57%, Impella-pre-PCI: 38%, p = 0.0053) and if revascularisation was incomplete (rS ≤ 8: 37%, rS > 8: 56%, p = 0.0099). Patients with both pre-PCI Impella implantation and complete revascularisation had significantly lower mortality (33%) than those with incomplete revascularisation and implantation post PCI (72%, p < 0.001). Conclusions: Our retrospective analysis suggests that complete revascularisation supported by an Impella microaxial pump implanted prior to PCI is associated with lower mortality than incomplete revascularisation in patients with AMI-CS.